Minangkabau migration to Tanah Gayo, Aceh: History, Factors, and Impacts - Iswanto, Sufandi; Kusnafizal, Teuku; Kamza, Muhjam; Haikal, Muhammad (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2022)
This research examines the migration of the Minangkabau to Tanah Gayo, Aceh. This research aims to describe the history of migration, the factors of migration, and the impact of the migration of the Minangkabau tribe to Tanah Gayo. The method used in this research is an ethnological research method with data sources through literature studies. This study shows that the history of migration of the Minangkabau tribe to Tanah Gayo started in 1915 (during the Dutch colonial period) and continued until post-independence. The Minangkabau tribe came in waves and generally as traders of spices and textiles. The factors that make the Minangkabau migrate to Tanah Gayo are due to economic factors by way of trading, and cultural factors also influence, namely because there is a matrilineal system. In addition, other factors are due to the philosophy of life that recommends migrating, and other factors are due to disputes in the area of ​​origin and the spreading of the Muhammadiyah organization. The impact of the presence of the Minangkabau tribe on the Tanah Gayo community is the condition of Tanah Gayo being multicultural, the recognition of the Muhammadiyah organization, Minang traders who have created a market, and the occurrence of cultural acculturation due to the marriage between the Gayo tribe and the Minangkabau tribe.